SMAD4 maintains the fluid shear stress set point to protect against arterial-venous malformations - Banerjee, Kuheli; Lin, Yanzhu; Gahn, Johannes; Cordero, Julio; Gupta, Purnima; Mohamed, Islam; Graupera, Mariona; Dobreva, Gergana; Schwartz, Martin A.; Ola, Roxana (The journal of clinical investigation, 2023)
Vascular networks form, remodel, and mature under the influence of both fluid shear stress (FSS) and soluble factors. Physiological FSS promotes and maintains vascular stability via synergy with bone morphogenic proteins 9 and 10 (BMP9 and BMP10). Conversely, mutation of the BMP receptors activin-like kinase 1 (ALK1), endoglin (ENG), or the downstream effector, SMAD family member 4 (SMAD4) leads to hereditary hemorrhagic telangiectasia (HHT), characterized by fragile and leaky arterial-venous malformations (AVMs). How endothelial cells (ECs) integrate FSS and BMP signals in vascular development and homeostasis and how mutations give rise to vascular malformations is not well understood. Here, we aimed to elucidate the mechanism of synergy between FSS and SMAD signaling in vascular stability and how disruption of this synergy leads to AVMs. We found that loss of Smad4 increased the sensitivity of ECs to flow by lowering the FSS set point, with resulting AVMs exhibiting features of excessive flow-mediated morphological responses. Mechanistically, loss of SMAD4 disinhibits flow-mediated KLF4-TIE2-PI3K/Akt signaling, leading to cell cycle progression–mediated loss of arterial identity due to KLF4-mediated repression of cyclin dependent Kinase (CDK) inhibitors CDKN2A and CDKN2B. Thus, AVMs caused by Smad4 deletion are characterized by chronic high flow remodeling with excessive EC proliferation and loss of arterial identity as triggering events.
Online veröffentlicht: 25. Juli 2023
Gesehen am 03.01.2024